Measuring Improvements in Access to Justice: Utilizing an A2J Measurement Framework for Comparative Justice Data Collection and Program Evaluation Across Canada - Lowenberger, Brea; Heavin, Heather; McCutcheon, Jessica; Nelson, Melissa (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2021)
Improving access to justice in Canada’s justice system is often the impetus for introducing new innovations or changing existing systems. However, measuring the effectiveness of these initiatives to improve access to justice is challenging without a common language to help identify and define the elements of access to justice, and without a common framework to help guide the measurement and evaluation of whether improvements are being realized. This paper seeks to contribute to the access to justice measurement discourse by highlighting an access to justice evaluation framework that has been developed with the triple aim objectives of improving population access to justice, improving user experience of access to justice, and improving costs. We also demonstrate how this framework has been used as part of the planning and evaluation of the Listen Project in Saskatchewan, illustrating how this framework can be universally adapted to other projects and initiatives throughout the justice sector.